2015
DOI: 10.18632/oncotarget.3274
|View full text |Cite
|
Sign up to set email alerts
|

By activating matrix metalloproteinase-7, shear stress promotes chondrosarcoma cell motility, invasion and lung colonization

Abstract: Interstitial fluid flow and associated shear stress are relevant mechanical signals in cartilage and bone (patho)physiology. However, their effects on chondrosarcoma cell motility, invasion and metastasis have yet to be delineated. Using human SW1353, HS.819.T and CH2879 chondrosarcoma cell lines as model systems, we found that fluid shear stress induces the accumulation of cyclic AMP (cAMP) and interleukin-1β (IL-1β), which in turn markedly enhance chondrosarcoma cell motility and invasion via the induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 71 publications
3
34
0
Order By: Relevance
“…A recent study of chondrosarcoma cell lines reported that interstitial flow and fluid shear stress induced MMP‐7 expression and thereby enhanced invasion via the PI3‐K, ERK1/2 and p38 signaling pathway . This is similar to the pathway investigated by Shi et al .…”
Section: Discussionsupporting
confidence: 75%
“…A recent study of chondrosarcoma cell lines reported that interstitial flow and fluid shear stress induced MMP‐7 expression and thereby enhanced invasion via the PI3‐K, ERK1/2 and p38 signaling pathway . This is similar to the pathway investigated by Shi et al .…”
Section: Discussionsupporting
confidence: 75%
“…The C‐terminal domain of HSPG2, Dm IV‐3, can be cleaved by MMP7, which will favor cell dispersion and migration (Grindel et al, ). Although there was no evidence for the direct regulation of MMP7 activities by substrate stiffness, the other mechanical stimulus, matrix stress, induced the activation of MMP7 in chondrosarcoma cells (Guan et al, ). The results of that study showed that shear stress could resulted in accumulation of cyclic AMP, which in turn, led to the increased expression of MMP7 by the activation of several intracellular signaling pathways, including PI3‐kinase, ERK, and p38.…”
Section: Discussionmentioning
confidence: 99%
“…When exerted directly on cancer cells, shear stress can increase cells’ invasive and metastatic potential. Wang P and Guan PP et al indicated that shear stress with 2 dyn/cm 2 increased the release of cyclic AMP and interleukin-1β via the induction of MMPs (MMP-1, MMP-7 and MMP-12) in PI3-K and ERK1/2-dependent manner, which significantly promoted motility and invasion of chondrosarcoma cells [39, 40]. …”
Section: Discussionmentioning
confidence: 99%